Fostering Cultural Insight: Exploring Multicultural Education through the Lens of the Younger Generation - Andi Anugrah Surya Ardhy (Al'Adalah, 2024)
This study aims to evaluate and analyze students' perceptions of multicultural education at IAIN Manado, focusing on how well these principles are implemented in practice. This study used a quantitative research method using a questionnaire as the main instrument to collect data from 61 participants. Data were analyzed using descriptive statistical analysis, which included frequency distribution, average score, and standard deviation. The study found that most participants felt proud and interested in learning about cultural and religious diversity at IAIN Manado. They also feel more open and tolerant of cultural and religious differences. The study results show that 87.93% of the younger generation have a positive perspective on IAIN Manado as a model of multicultural education in North Sulawesi. This study also provides insight into the effectiveness of multicultural education in increasing students' knowledge, attitudes, and behavior toward cultural and religious diversity. The results of this study can be helpful for policymakers and educators to develop effective strategies for promoting multicultural education in other educational institutions. However, further research is needed to explore the long-term impact of multicultural education on students' attitudes and behavior toward cultural and religious diversity.